Epidemiological characteristic of salmonellosis in Serbian areas of Kosovo and Metohija - Stevanović Jasmina; Milić Marija; Antonijević Aleksandar (Praxis Medica, 2017)
Salmonellosis are food-borne toxinfections flowing with the clinical picture of acute enterocolitis, and are caused by non-typhoid salmonella (Salmonella food poisoners). The main objective of the study was to identify the most important epidemiological characteristics of salmonellosis in Serbian areas of Kosovo and Metohija. We used the data or reporting of infectious diseases, reports on infectious diseases (seven-day, month, year) of the Public Health Pristina in Kosovska Mitrovica. In our research we used epidemiological Studies of cross-section (cross-sectional) Between 2003-2015.god. Kosovo and Metohija (Serbian middle) registered 250 cases of salmonella. The average incidence in the reporting period was 12.35 / 10,0000. Analysis of age distribution revealed that the most common incidence in people aged 20-29 years, and the rarest people ages 15-19 godina. salmoneloze occur throughout the year showing seasonal variations. The trend in the incidence of salmonellosis is decreasing in the territory of Kosovo and Metohija Based on the results of our study we can conclude that a significant salmonellosis both public health and animal health but also economic problem. Epidemiological situation with regard to salmonella requires intense activity in the field of food safety not only medical services, but also veterinarians and veterinary and sanitary inspection.